Interictal SPECT in the presurgical evaluation in epileptic patients with normal MRI or bilateral mesial temporal sclerosis SPECT intercrítico na avaliação pré-cirúrgica de pacientes epiléticos com ressonância magnética normal ou esclerose mesial temporal bilateral - Lucia H.N. Marques; José R.L. Ferraz-Filho; Mário L.M. Lins-Filho; Marina G. Maciel; Rafael Yoshitake; Sarah V. Filetti (Arquivos de Neuro-Psiquiatria)
The aim of this study was to evaluate the sensitivity of interictal compared to ictal SPECT in the lateralization of the epileptogenic focus in refractory temporal lobe epilepsy (TLE) patients that present with normal magnetic resonance imaging (MRI) or bilateral mesial temporal sclerosis (MTS). Thirty patients with TLE, for whom MRI examinations were normal or who presented with bilateral MTS, were retrospectively studied. Using a confidence interval of 95% and a level of significance for p-value <0.05, an estimated agreement rate of 73% with a minimum agreement rate of 57% was calculated comparing interictal and ictal SPECTs. In conclusion the interictal SPECT is only useful when associated with the ictal SPECT and does not substitute it in the localization of epileptogenic areas in patients with normal MRI or bilateral MTS. O objetivo deste estudo foi avaliar a sensibilidade do SPECT interictal, em relação ao ictal, na lateralização do foco epileptogênico, de pacientes com epilepsia refratária de lobo temporal (ELT) que apresentam ressonância magnética (RM) normal ou esclerose mesial temporal (EMT) bilateral. Foram estudados retrospectivamente 30 pacientes com ELT, nos quais os exames de RM eram normais ou apresentavam EMT bilateral. Avaliada a sensibilidade do SPECT interictal em relação ao ictal, obtivemos taxa estimada de acerto de 73% com taxa mínima de acerto de 57%, adotando intervalo de confiança de 95% e índice de significância p<0,05. Conclui-se que o SPECT interictal é necessário apenas quando associado ao SPECT ictal, e não substitui a realização do ictal na localização da AE em pacientes com RM normal ou EMT bilateral.